A systemic increase in the recombination frequency upon local infection of Arabidopsis thaliana plants with oilseed rape mosaic virus depends on plant age, the initial inoculum concentration and the time for virus replication - Yao, Youli; Kathiria, Palak; Kovalchuk, Igor (Frontiers in Plant Science, 2013)
In the past, we showed that local infection of tobacco leaves with either Tobacco mosaic virus (TMV) or Oilseed rape mosaic virus (ORMV) resulted in a systemic increase in the homologous recombination frequency (HRF). Later on, we showed that a similar phenomenon occurs in Arabidopsis thaliana plants infected with ORMV. Here, we tested whether the time of removing the infected leaves as well as viral titer have any effect on the degree of changes in HRF in systemic tissues. An increase in HRF in systemic non-infected tissues was more pronounced when the infected leaves were detached from the infected plants at 60-96 hours post infection, rather than at earlier time. Next, we found that exposure to higher concentrations of inoculum was much more efficient in triggering an increase in HRF than exposure to lower concentrations. Finally, we showed that older plants exhibited a higher increase in HRF than younger plants. We found that an increase in genome instability in systemic tissues of locally infected plants depends on plant age, the concentration of initial inoculums and the time of viral replication.